Uncovering circuit mechanisms of current sinks and sources with biophysical simulations of primary visual cortex - Rimehaug, Atle E; Stasik, Alexander J; Hagen, Espen; Billeh, Yazan N; Siegle, Josh H; Dai, Kael; Olsen, Shawn R; Koch, Christof; Einevoll, Gaute T; Arkhipov, Anton (eLife, 2023)
Local field potential (LFP) recordings reflect the dynamics of the current source density (CSD) in brain tissue. The synaptic, cellular, and circuit contributions to current sinks and sources are ill-understood. We investigated these in mouse primary visual cortex using public Neuropixels recordings and a detailed circuit model based on simulating the Hodgkin–Huxley dynamics of >50,000 neurons belonging to 17 cell types. The model simultaneously captured spiking and CSD responses and demonstrated a two-way dissociation: firing rates are altered with minor effects on the CSD pattern by adjusting synaptic weights, and CSD is altered with minor effects on firing rates by adjusting synaptic placement on the dendrites. We describe how thalamocortical inputs and recurrent connections sculpt specific sinks and sources early in the visual response, whereas cortical feedback crucially alters them in later stages. These results establish quantitative links between macroscopic brain measurements (LFP/CSD) and microscopic biophysics-based understanding of neuron dynamics and show that CSD analysis provides powerful constraints for modeling beyond those from considering spikes.
Keywords: local field potential; current source density; spikes; large-scale biophysically detailed network model; experimental validation